Respuesta del cultivo de maíz (Zea mays) híbrido Advanta a varias dosis de NPK y fertilizantes foliares - Loor Lucas, Ángel Alejandro (2023)
The application of fertilizers is an essential action in the production process of corn, because it is a crop with a high nutrient demand and the soil tends to show nutritional declines, limiting its optimal development. The objective of the research was: to determine the effectiveness of various doses of Nitrogen, Phosphorus and Potassium (NPK) and foliar fertilizers on the production and yield of Advanta Hybrid maize (Zea mays) in the Carrizal River valley. The experiment was carried out at Escuela Superior Politécnica Agropecuaria de Manabí "Manuel Félix López", a Randomized Complete Block Design (DBCA) was used with nine treatments, plus a control with three replicates, providing a total of 30 experimental units, with 120 plants each, the data analysis was carried out with ANOVA, the separation of means with Tukey at 5%. Variables such as plant height, stem diameter, ear insertion height, ear length, ear diameter, rows of grains per ear, number of grains per row, number of grains per ear, weight of 100 grains and yield in kgha-1. The results showed that the 180/80/120 dose of NPK per hectare and the foliar fertilizer Metalosato Crop up of treatment 6 increased the corn yield, however, due to production costs, the T1 treatments (Bayfolan 9-9- 7) with a dose of 160/60/90, and T4 (Bayfolan 9-9-7) with a dose of 180/80/120 had a benefit/cost ratio of 1.71 with a profitability of 71.1%. Therefore, the use of these foliar fertilizers in corn crops is recommended.